Band flattening and phonon-defect scattering in cubic SnSe–AgSbTe2 alloy for thermoelectric enhancement. (January 2021) - Wang, Hongxiang; Hu, Haoyang; Man, Na; Xiong, Chenglong; Xiao, Yukun; Tan, Xiaojian; Liu, Guoqiang; Jiang, Jun
Abstract: With multiple band valleys and intrinsic low thermal conductivity, rock-salt SnSe possesses great potential as a promising thermoelectric material. Herein, we prepare cubic SnSe–AgSbTe2 alloy and demonstrate the synergistically optimized electronic and thermal transport properties. For the former, AgSbTe2 alloying can tune the Fermi surface and promote the band flattening, concurrently improving the density of state effective mass and carrier concentration. For the latter, the strong phonon-defect scattering caused by AgSbTe2 alloying contributes to a great reduction of lattice thermal conductivity. Collectively, an obviously enhanced ZT max of 1.00 at 820 K and ZT ave of 0.70 (300–820 K) are achieved in Sn0.5 Ag0.25 Sb0.25 Se0.5 Te0.5 . Moreover, AgSbTe2 alloying can also improve the mechanical property and the Vickers hardness reaches 1.90 Gpa, which is over four times higher than that of pristine SnSe. Graphical abstract: Image 1 Highlights: Rock-salt SnSe-AgSbTe2 alloy is synthesized. AgSbTe2 alloying introduces band flattening and multiple defect-phonon scattering. A ZT max of 1.0 at 820 K and a ZT ave of 0.7 between 300–820 K are obtained. The corresponding Vickers hardness significantly increases to 1.90Gpa.